Associations between fine particulate matter constituents and hospital outpatient and emergency room visits in Shanghai, China. (15th September 2021) - Yang, Dandan; Liu, Cong; Peng, Li; Ye, Xiaofang; Zhou, Ji; Mao, Zhuocheng; Yang, Sixu; Kan, Haidong; Fu, Qingyan; Chen, Renjie
Abstract: Background: Scarce evidence is available on the health effects of various chemical constituents of PM2.5 on hospital visits in China. Objectives: To examine the short-term associations between a wide range of PM2.5 constituents and hospital outpatient and emergency room visits in Shanghai. Methods: We obtained daily concentrations of PM2.5 total mass, organic carbon (OC), elemental carbon (EC), eight water-soluble ions and thirteen elemental constituents between January 1, 2014 and December 31, 2015. We analyzed the data using over dispersed generalized additive models with Poisson regression. Single-constituent, PM2.5 -adjusted and constituent-residual models were built respectively to assess the associations. Exposure-response curves for the PM2.5 constituents with robust effects were graphed. Results: The average daily mean PM2.5 concentration was 63.3 μg/m 3 in Shanghai during the study period. An interquartile range (IQR) increase in PM2.5 was associated with a 2.57% (95% confidence interval [CI]: 1.28%, 3.87%) increase in outpatient visits, and a 3.60% (95% CI: 2.16%, 5.03%) increase in emergency room visits. We observed robust and positive associations between Mg 2+, Ca 2+, six elemental components (Ca, Mn, Fe, Zn, Ga and Se) and outpatient visits. OC, EC, Cl −, Mg 2+, Ca 2+ and ten elemental components (Ca, Cr, Mn, Fe, Zn, Ga, As, Se, Pb, and Ni) were significantly and positively associated with emergency room visits. The exposure-response relationships were positive and generally linear for the above constituents. Conclusions: This time-series study in Shanghai demonstrated significant associations between various carbonaceous, water-soluble and elemental constituents of PM2.5 and hospital visits, providing evidence for source-specific control of particulate air pollution. Graphical abstract: Image 1 Highlights: Scarce evidence on the health effects of PM2.5 constituents on hospital visits. Mg 2+, Ca 2+ and six elemental constituents linked with outpatient visits. Carbonaceous and ten elemental constituents associated with emergency room visits. Positive and linear exposure-response relationship curves for these constituents.